Stereoselective Michael Halogenation Initiated Ring Closure (MHIRC) Synthesis of Spirocyclopropanes from Benzylidenemalononitriles and 3-Arylisoxazol-5(4H)-ones - Vereshchagin, Anatoly N.; Elinson, Michail N.; Korshunov, Alexander D.; Anisina, Yuliya E.; Novikov, Roman A.; Goloveshkin, Alexander S.; Bushmarinov, Ivan S.; Zlotin, Sergey G.; Egorov, Mikhail P. (Synlett, 2016)
The new chemical cascade reaction was found: the direct formation of substituted 4-oxo-2,7-diaryl-5-oxa-6-azaspiro[2.4]hept-6-ene-1,1-dicarbonitriles from benzylidenemalononitriles and 3-aryl-2-isoxazol-5(4H)-ones. The action of bromine on the equimolar mixture of benzylidenemalononitrile and 3-aryl-2-isoxazol-5(4H)-one in the basic alcohol solution results in stereoselective formation of spirobicycle containing the 2-isoxazolin-5-one and the cyclopropane fragments in 53–92% yields. Thus, the new simple and efficient ‘one-pot’ approach to substituted (2R*,3R*)-4-oxo-2,7-diaryl-5-oxa-6-azaspiro[2.4]hept-6-ene-1,1-dicarbonitriles was found directly from simple and reasonable starting compounds as benzylidenemalonitriles and 3-aryl-2-isoxazol-5(4H)-ones.
Keywords: MHIRC reaction; cyclopropane formation; 3-aryl-2-isoxazolin-5(4H)-ones; benzylidenemalononitriles; 5-oxa-6-azaspiro[2.4]hept-6-enes